Serum Transaminase m Diphtheritic Myocarditis - Djauhar Ismail; Utomo Utomo; Suharjanto Suharjanto (Paediatrica Indonesiana, 1976)
Ninety-one cases out of 102 diphtheritic children admitted to the University of Gadjah Mada Hospital were studied, correlating enzyme levels (SGOT and SGPT) with ECG findings. The results showed that there was a correlation between the SOOT value and the severity of the ECO abnormalities. Beside ECO, the determination of serum transaminase should be considered as an adjunct laboratory examination in evaluating the diagnosis and prognosis of diphtheritic myocarditis.